Environmental life cycle assessment for a cheese production plant towards sustainable energy transition: Natural gas to biomass vs. natural gas to geothermal. (1st December 2020) - Tarighaleslami, Amir H.; Ghannadzadeh, Ali; Atkins, Martin J.; Walmsley, Michael R.W.
Abstract: The dairy processing industry is considered as one of the most electricity demanding industry among the process industries in New Zealand, which utilises fossil fuels for both process heat and utility generation including electricity. Fossil fuel combustion inherently produces and releases harmful chemicals to the environment as well as causing other environmental impacts, which make it essential to move towards renewable energy resources. This paper compares two renewable energy options to be introduced to the energy mix in order to moderate the environmental impacts of cheese production in a dairy processing factory during the energy transition period. Environmental Life Cycle Assessment (LCA) is used in conjunction with the concept of Cumulative Exergy Demand as an aggregated parameter in order to evaluate the environmental sustainability of the proposed energy mix. LCA confirms that without retrofitting the core of the cheese processing technology at this stage, it is possible to reduce several environmental impacts through the step-wise introduction of renewable energy into the energy mix. At each stage, 33% renewable energy is introduced to the energy mix where four different energy transition scenarios were investigated. The scenarios were supported by Monte Carlo simulation, which proves each defined energy transition scenario is sensitive to the step changes. In addition, it quantifies the independency of each scenario. The results showed that out of the 12 studied environmental impact categories, the natural gas based scenario, Scenario 1, has the lowest Human Health – Photochemical Oxidant Formation potential impact (1.44E-11 DALY), whereas renewable energy options (biomass and geothermal) have lower burdens regarding the other environmental impact categories. Having compared the scenarios associated with biomass and geothermal, it is observed that the geothermal-based scenarios have lower environmental burdens regarding the majority of impact categories. Highlights: Environmental impacts of energy transition scenarios on cheese factory were studied. Monte Carlo simulations confirmed the independency of energy transition scenarios. Exergy-aided LCA was performed supported by Monte Carlo simulations. Geothermal scenarios had lowest burdens for majority of impacts e.g. Climate Change. Natural gas-based scenarios had the lowest Photochemical Oxidant Formation.